Culture and dignity dialogues between the Middle East and the West - Nader, Laura (Wiley-Blackwell, 2013)
"In Culture and Dignity - Dialogues between the Middle East and the West, renowned cultural anthropologist Laura Nader examines the historical and ethnographic roots of the complex relationship between the East and the West, revealing how cultural differences can lead to violence or a more peaceful co-existence. Outlines an anthropology for the 21st century that focuses on the myriad connections between peoples--especially the critical intercultural dialogues between the cultures of the East and the West Takes an historical and ethnographic approach to studying the intermingling of Arab peoples and the West. Demonstrates how cultural exchange between the East and West is a two-way process Presents an anthropological perspective on issues such as religious fundamentalism, the lives of women and children, notions of violence and order "--